Evaluation of the effectiveness of potassium bicarbonate and sunflower oil in controlling powdery mildew disease caused by the fungus Erysiphe cichoracearum on squash squash under protected cultivation conditions in 2012 and 2013. (Journal of the College of Basic Education, 2022)
The study was conducted in a plastic house , college of Agriculture university of Baghdad in 2012 and 2013 seasons to evaluate the efficiency of Potassium bicarbonate and Sunflower oil separately and in combination for controlling Powdery mildew on Squash caused by Erysiphe cichoracearum under natural infection . Plant foliage was sprayed with the different treatments 6 time for 6 weeks .Results showed that all treatments reduced significantly the disease severity with obvious superiority of the combination between bicarbonate with Sunflower oil .The disease Severity in potassium bicarbonate at 3 and 5g /L combined with 5ml /L of sunflower oil wer 3% and 4% compared to 45%, 49%, and 42% for the tow concentrations of bicarbonate 3 and 5 g/L and sunflower oil separately , and with 90% in control treatment in 2012 season ,7% and 2% compared with 43% ,48%, 41% for the same previous treatments respectively in 2013 season compared to 91% in control . The disease severity was found to be zero % with the fungicide Mistek at 0.4 ml/ L for the tow seasons . The results also revealed gradual development of the disease on squash plants which attained to 100% and 94% in the tow season of 2012 and 2013 respectively .